Implementasi Kurikulum Darurat Dimasa Pandemi Covid-19 Di Kabupaten Kepualaun Sula - Adam, Adiyana; Kamaluddin, Nuraini; Mubin, Hendra (Peneliti.net, 2024)
This study aims to find out the implementation of emergency curriculum in Madrasah Tsanawiyah Negeri I Kepulauan Sula during the COVID-19 pandemic, involving the Head of Madrasah, Wakamad Kurikulum, and PAI teachers. Socialisation strategies, meetings, and collective decisions are described to overcome learning challenges during the pandemic. Discovery learning was chosen for emergency curriculum implementation, customised for online and offline learning. The allocation of BOS funds to purchase internet data is a crucial step to ensure access to online learning. Learning evaluation involves question and answer sessions and assignments, with teachers playing a critical role in providing feedback. Although technical constraints arise regarding the availability of student facilities, a group approach is used for students without Android phones. Discovery learning is relevant in developing students' competencies, and BOS funds support access to online learning. Despite modifications, discovery learning can still be adapted through technology, ensuring an interactive and exploratory learning experience for students.